Monday

July 28, 2014

July 28, 2014

Posted by **Cora** on Wednesday, October 29, 2008 at 5:19pm.

(X^2-1) (x^2+-9) (I got x^3+-12)

(x^2+-9)-(x+-3) (I got x+12)

f(g(x)) F=3x-4 G=(-x^2)I got -3x^3+4x^2

f(g(x))F=-2x G+-2x^2+3 I got 4x^3+-6x

- Algebra -
**drwls**, Wednesday, October 29, 2008 at 5:35pmYour answers almost seem like wild guesses. You appear to be in serious need of private tutoring until you grasp basic algebraic rules.

Why do you have both a + and- in front of the 9 in the first problem and in front of the 3 in the second problem?

(x^2-1) (x^2-9) = x^4 - 10x^2 +9

x^2 -9 -(x -3) = x^2 -x -6

If f=3x-4 and g=(-x^2)

f[g(x)] = -3x^2 -4

g[f(x)] = -(3x-4)^2 =-9x^2 +24x -16

**Related Questions**

Algebra - I was wondering if someone could check over these answers for me. Find...

Algebra - 1. Find the slope of the graph of the linear function f with f(0)=4 ...

English - Now, let's check how well you can use the expressions you've learned. ...

Math HELP - I have my answers at the bottom but please do these questions so I ...

Algebra - Hi, could someone possibly check my answers to these algebra questions...

Chemistry (URGENT) - I have a test soon. If you can help me with these questions...

Math - Please Check My Answer I don't know if they are right or wrong and if ...

English - You are going to take a quiz. I'll distribute exam papers. You should...

Math - Can someone please check my answers below for accurateness? The ...

English - procedure: Formative Test Now. let's check how well you can use the ...